SISTEM MONITORING KETERSEDIAAN BAHAN BAKU COR BETON MENGGUNAKAN METODE MARKET BASKET ANALYSIS - Rometdo Muzawi; Tashid Tashid; Mahadir Nasution (Prodi Sistem Informasi Universitas Dharma Andalas, 2019)
Cast concrete is very important in building physical buildings, both for the construction of houses, hotels, bridges, apartments and other physical buildings. The concrete cast material is the most chosen by the community in building buildings because it is easily formed according to the needs of construction and has a strong strength and is resistant to high temperatures.